THE UNIVERSALS OF POETIC TRANSLATION: A STUDY BASED ON UZBEK TRANSLATIONS OF ENGLISH POETRY FROM THE 20TH CENTURY - Bekmurzaeva Umida (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article investigates the universals of poetic translation through the lens of 20th-century English poetry translated into Uzbek. By examining over 120 translated poems by prominent English-language poets such as W. B. Yeats, T. S. Eliot, Sylvia Plath, and Robert Frost, and their Uzbek renditions by major Uzbek translators, this study identifies recurring translation strategies and the underlying linguistic, cultural, and stylistic transformations. A combination of comparative stylistics, corpus linguistics, and qualitative discourse analysis is applied. Findings reveal that poetic translation often conforms to universals such as explicitation, simplification, and stylistic leveling, while cultural nuances and prosodic forms are domesticated to align with Uzbek literary aesthetics.